(untitled) (Archives of Mechanics - Test, 2000)
Various existing constitutive equations aiming at the description of the time-dependent deformation behavior for a wide range of stress below and over the elastic limit, i.e. the yield stress are reviewed in detail. It is suggested that the plastic stretching and the creep stretching have to be treated as independent quantities since they have substantially different physical properties and that a stress goes out from the yield surface at a high rate of deformation since a plastic deformation is suppressed by a high viscous resistance and then the yield surface is kept unchanged. The subloading surface model [1-3] would satisfy these requirements since it does not premise that a stress is on the yield surface even in the plastic loading process. In this article, based on the extended subloading surface model [4] which is capable of describing not only monotonic but also cyclic loading behavior, the generalized time-dependent elastoplastic constitutive equation is formulated allowing the stress go out from the yield surface by letting the plastic deformation be suppressed at a high rate of deformation and introducing the creep stretching which proceeds with time in addition to the elastic and the plastic stretching.